ANALISIS PEMAKAIAN SHUUJOSHI ZE DAN ZO DALAM KALIMAT BAHASA JEPANG - Isfaroh, Astnahati; Surono, Surono; Rosliana, Lina (Japanese Literature, 2015)
The purpose of this research is to identify the use of shuujoshi ze and zo inHakkenden comic so that the readers understand its use, especially in Japanesecomic. The data of the research is a Japanese comic by Miyuki Abe entitled"Hakkenden" volume 1-8.The method used in this research are descriptive method and deletion technique.Descriptive method and deletion technique are applied to identify the degree ofsignificance of the unit being deleted.The results of the research related to the application of shuujoshi ze is applied inmaking statement or used in changing statement into interjection and specifyingparticular unit of the statement to attract listeners. Shuujoshi ze also showing offthe speaker's wants, shuujoshi ze strengthens the speaker's suggestion towardslisteners. Shuujoshi zo is applied in showing imperative statement or threat. It isalso found that it strengthens the function mentioned and adding strength to theword to emerge the speaker's bravery or urging the speaker himself. The result ofdeletion technique analysis shows the insignificance of the shuujoshi ze and zo. Itmeans without shuujoshi ze and zo a sentence is still grammatical.